Can neurological evidence refute free will? The failure of a phenomenological analysis of acts in Libet’s denial of «positive free will» - Seifert, Josef (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In a first part of this paper I expound briefly the essential characteristics of free will. The second part deals with the objections of Benjamin Libet, allegedly based on brain-scientific foundations, against «positive free will». The third and main part shows that Libet’s anti-positive-free-will-position is due to an almost complete failure of a phenomenology of the conscious acts that precede, accompany and follow voluntary movement. The fourth part defends the thesis that Libet’s experimental results, far from supporting his philosophical stance, contain strong empirical confirmations of human free will, which, apart from a phenomenology of human acts, becomes further clear upon noticing striking philosophical deficiencies and contradictions in his distinction between ‘positive’ and ‘negative’ free will. The conclusions summarize the results, according to which positive free will and causality through freedom exist and are confirmed by Libet’s and other test results. Free will is the primary and model case of an efficient cause, instead of contradicting or challenging the principles of causality and of sufficient reason
Keywords: neurology; free will; libet; free acts; free causation; undeterminism; determinism